Effect of substituting rice meal by sweet potatoes, wheat and barley flour on rice bread producing - Abdeen, E. M. I.; Agag, M. E.; Abu El-Azm, Y. Z. (2009)
In order to get a wide variety of nutrients on our daily consumption of bread, avoid metabolic syndrome cases, to face climate change, and Bio-fuel which planted for producing it from grains, and cultivate Gatropha plant. The local different carbohydrates of cereals are solution. Replace as many refined carbohydrates of whole grains of rice meal, barley flour, and sweet potatoes as vegetable carbohydrates were studied. Barley yields of hulls, bran, and total flour of three cultivars milled from seeds and whole grain (de hulling by rice polisher machine) were studied.
Includes references.
Summary in Arabic.
1
Keywords: Bread industry; Barley; Rice flour; Bread -- Composition